White as the shroud: India, Pakistan and war on the frontiers of Kashmir - MacDonald, Myra (Hurst & Company, 2020)
Between South and Central Asia, in the high mountains and cold deserts, India, Pakistan and China have fought brutal wars over barren, uninhabited territory in a bid for control over their national peripheries, including Xinjiang and Tibet in China, and Jammu and Kashmir on the Indian subcontinent. White as the Shroud explores this broader story through the most surreal of such conflicts: the Siachen war, fought between India and Pakistan for control of the eponymous glacier. The tale of Siachen highlights the absurdity of seeking hard borders in such desolate mountains, as well as the brutality of high-altitude warfare—more soldiers were killed by the weather and terrain than by the fighting. As one of the few people to have visited both sides of the glacier, Indian and Pakistani, Myra MacDonald provides a first-hand view of the battlefield and a wealth of eyewitness testimony from combatants. She sets this account in the overarching narrative of the Kashmir conflict, India’s defeat by China in 1962, and the 1999 India-Pakistan Kargil war. White as the Shroud brings a fresh perspective to one of the most volatile corners of the world, raising questions about borders and the wars fought to defend them.